TINJAUAN IMPLEMENTASI PENGELOLAAN DANA DESA DIKECAMATAN SITINJAU LAUT BERDASARKAN PERATURAN BUPATI KERINCI NO 21 TAHUN 2019: Pebi Julianto - Julianto, Pebi (Qawwam : The Leader's Writing, 2021)
Review of the Implementation of Village Fund Management in Sitinjau Laut Subdistrict Based on the Kerinci Regent Regulation No 21 of 2019. The phenomenon that occurs in Sitinjau Laut Subdistrict has many problems, both in the areas of planning, implementation, administration, reporting, and village financial accountability. At the planning stage, the use of village funds tends to be more in the program to be implemented by the Village Head so that at the deliberation of the development plan, the impression of the community leaders present is only to listen and at the stage of discussing the plan to use village fund policies that are presented only certain people The results of the discussion of the work plan for the Use of Village Funds are not discussed in general so that the community does not even know that the village has received large funding assistance from the local government through the Regional Budget (APBD). village officials regarding village fund management policies. This study aims to determine how the priority of the use of village funds in Sitinjau Laut Subdistrict where village funds are used to finance government administration, development implementation, community development, and community empowerment. The research method used is qualitative, the data source in this study were 9 people. The data taken are primary data and secondary data.